Folkloristični portret Gregorja Kreka - Stanonik, Marija (Traditiones (Ljubljana), 2006)
Three of the most prominent Slovenian professors teaching at the University of Graz were primarily Slavic philologists Gregor Krek (1840-1905), who in 1871 become associate professor and three years later, in 1874, full professor, was the first certificated Slavic philologist. The article focuses on Krek as the founder of Slavic studies at the University of Graz. As is evident from his scientific bibliography the study of Slavic languages was one of philological disciplines that were still closly connected at the time.
Keywords: Krek, Gregor, 1840-1905; ethnology; etnologija; folkloristics; folkloristika; slovanska filologija; mitologija; mythology; biografije